«Le sentiment de la langue » dans l’œuvre de Richard Millet - Prosowska, Monika (Studia Romanica Posnaniensia, 2006)
A key concept is this work is a term coined by Richard Millet and used in the title of his essay Le sentiment de la langue ("Feeling for language"). It allows for a broad interpretation of the author's fiction, in which language experience is in the center of attention. This language experience is examined on the level of narration techniques, the process of establishing the speaker's voice, on the ethics of social relations as expressed by language, and on the status of the novel itself. Through a binary presentation of these issues, Millet does not strive after solutions, but rather aspires to highlight the dynamism of the phenomena of language and literature.